AGRI-HORTI SYSTEMS AND WEED MANAGEMENT PRACTICES EFFECT ON GROWTH AND YIELD OF MUNGBEAN [VIGNA RADIATA (L.) WILCZEK] - M. K. SINGH; KUMAR , PRAVIN; S. K. PRASAD (The Bioscan, 2014)
A field experiment was conducted during kharif season of 2010 at Rajiv Gandhi South Campus (Banaras Hindu University), Barkaccha, Mirzapur to study the effect of agri-horticultural system [custard apple (Annona squamosa) and guava (Psidium guajava)] and weed management practices [pendimethalin 1000 g a.i./ha (pre emergence), imazethapyr 125 g a.i./ha (post-emergence), weedy check, 1-hand weeding (20 DAS)] on mungbean. Custard apple based agri-horti system recorded higher weed-density and -biomass over guava agri-horti system. But growth, yield attribute and yield of mungbean did not influenced with agri-horti system. Significantly lowest density and biomass of weeds observed under 1-hand weeding. Imazethapyr 125 g/ha effectively reduced density and biomass of Trianthema monogyna, Cynodon dactylon and Echinochloa colonum and total weeds as compared to pendimethalin 1000 g/ha. Density and biomass of Cyperus rotundus did not differed significantly with herbicides. Application of imazethapyr 125 g/ha and 1-hand weeding produced at par plant height, number of branches/plant and harvest index of mungbean.